Influence of Ca/Al ratio on physical and dielectric properties of Al2O3/CaO-B2O3-SiO2 glass-ceramics composite coatings prepared by high enthalpy atmospheric plasma spraying. Issue 4 (April 2022) - Li, Qi; Xie, Jianliang; Hu, Jin; Wang, Xin; Yu, Chengyong; Jiang, Shaoliang; Liu, Peng; Sun, Chengli; Li, En; Deng, Longjiang
Abstract: The dielectric layer plays a key role in regulating electromagnetic wave broadband scattering based on meta-surface technology. Herein, the physical properties of composite powder, prepared by spray drying of CaO-B2 O3 -SiO2 (CBS) glass-ceramic powder and Al2 O3 in different mass ratios, are systematically investigated. Meanwhile, a high enthalpy atmospheric plasma spraying equipment is utilized to prepare CBS/Al2 O3 composite coatings, and the morphology, physical properties and dielectric properties of the composite coating are analyzed. The XRD and DSC data of the composite coating reveal that the crystallization behavior of β-CaSiO3 and CaB2 O4 gradually disappear with the increase of Al2 O3 content. Hence, only CaAl2 Si2 O8 phase is observed during heat treatment. The experimental results confirm that the dielectric properties of CBS/Al2 O3 composite coating conform to the rule of mixture for composite materials. Also, the dielectric properties are affected by porosity and crystallization rate.